MATHEMATICAL PROGRAMMING FOR MEASURING EFFICIENCY IN EDUCATIONAL SECTOR - ILEANA CASTILLO ARIAS; GABRIELA MARÍN RAVENTÓS (Revista de Matemática: Teoría y Aplicaciones, 2017)
In this paper an analysis of technical and scale efficiency of the academic units of the University of Costa Rica is presented. The methodology used is data envelopment analysis (DEA), since it allows to measure relative efficiency and provides information on how to improve each academic unit that is inefficient. The results are reported for three groupings: one based on the training process, another based on size (according to three inputs) and the third based on the knowledge area. Three inputs and three outputs are used. A sensitivity analysis through the development of four models is performed. The emphasis is on the mathematical model used, the output-oriented model, with variable returns of scale, solved each time with normalized data.